We can multiply first equation x + 3y = -14 by 2 to get rid of varibale "x"
Solution:
Given that, the system of equations are:
x + 3y = -14 ----- eqn 1
2x + y = -3 --------- eqn 2
We can solve by elimination method
For doing elimination, we have to make the any one of coefficient of variable same
Here, in eqn 1 we have 1 as coefficient for "x"
In eqn 2, we have 2 as coeficient for "x"
So, we can multiply eqn 1 by 2, to get rid of "x"
2(x + 3y = -14)
2x + 6y = -28 ------- eqn 3
If we subtract eqn 2 from eqn 3, we will get the solution
2x + 6y = -28
2x + y = -3
( - ) ----------------
5y = -25
y = -5
Substitute y = -5 in eqn 1
x + 3(-5) = -14
x -15 = -14
x = 1
Thus the solution is x = 1 and y = -5. So we have multiplied equation 1 by 2 to get of varibale "x" and solved the equations